Modified AES Cipher Round and Key Schedule - Edjie Malonzo De Los Reyes; Ariel M. Sison; Ruji Medina (IAES Indonesian Section, 2019)
In this paper, Advanced Encryption Standard was modified to address the lowdiffusion rate at the early rounds by adding additional primitive operationssuch as exclusive OR and modulo arithmetic in the cipher round. Furthermore,byte substitution and round constant addition were appended to the keyschedule algorithm. The modified AES was tested against the standard AESby means of avalanche effect and frequency test to measure the diffusion andconfusion characteristics respectively. The results of the avalanche effectevaluation show that there was an average increase in diffusion of 61.98% inround 1, 14.79% in round 2 and 13.87% in round 3. Consequently, the resultsof the frequency test demonstrated an improvement in the randomness of theciphertext since the average difference between the number of ones to zeros isreduced from 11.6 to 6.4 along with better-computed p-values. The resultsclearly show that the modified AES has improved diffusion and confusionproperties and the ciphertext can still be successfully decrypted and recoverback the original plaintext.